Factors Affecting Implementation of Pain Reassessment in Inpatient Unit at Balaraja Regional Hospital - Ngasu, Kristina Everentia; Restiana, Restiana (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Pain is a sensation of individual discomfort. Patients often experience pain, especially pain after undergoing surgery. Pain free is one of patient’s needs. Nurses should control and monitor the level of pain through pain reassessment, but this is not adequate. AIM: This study aims to get a picture about nurse’s knowledge, attitude and supervision, and its relationship to the implementation of pain reassessment. METHODS: A descriptive type of cross-sectional study was conducted among 36 inpatient’s nurses at Balaraja Regional Hospital applying total sampling technique. Data were collected using a self-made questionnaire, which passed validity and reliability test. Data entry and analysis were carried out using the Statistical Package for the Social Sciences with Chi-square test. RESULTS: Twenty-five (61.1%) nurses were in category good knowledge, 24 (66.7%) in category good attitude, 26 (72.2%) in good supervision, and 25 (69.4%) implementation of pain reassessment were in good category. There is no relationship between knowledge and implementation of pain reassessment (p = 0.467), but there is a relationship between attitude and implementation of pain reassessment (p = 0.020) and between supervision and implementation of pain reassessment (p = 0.039). CONCLUSION: This research concludes that there is no relationship between respondent knowledge and implementation of pain reassessment and there is a relationship between respondent’s attitude and supervision with the implementation of pain reassessment in Inpatient Unit at Balaraja Regional Hospital in 2019. Nursing Management, to provide this information or in-service training for respondents to increase knowledge and attitude and to have a tight supervision, especially for respondents at practical nurses level one (PK-1) so that it is expected that the implementation of pain re-assessment will be better.